Features of metabolic effects of lisinopril in patients with hypertension and abdominal obesity - Шаповалова, С. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The article presents the results of a 1-month treatment of patients with moderate hypertension and metabolic disorders by lisinopril. The findings show a high antihypertensive activity of the drug, which is combined with the correction of glycemic and lipid profiles in patients with different degrees of manifestation of the metabolic syndrome. The use of lisinopril during the 30 days allowed reducing significantly cholesterol and triglycerides in obese patients; also, a trend was shown to the increase of leptin level and the decrease of the level of tolerance to glucose. Maximal significant dynamics of metabolic parameters in the group of persons with hypertension and abdominal obesity (with no signs of impaired glucose tolerance) testifies to the effectiveness of monotherapy with lisinopril in patients with primary manifestation of lipid imbalance.